Green preparation, characterization, evaluation of anti-melanogenesis effect and in vitro/in vivo safety profile of kojic acid hydrogel as skin lightener formulation. Issue 17 (23rd November 2022) - Gatabi, Zahra Rezanejad; Saeedi, Majid; Morteza-Semnani, Katayoun; Rahimnia, Seyyed Mobin; Yazdian-Robati, Rezvan; Hashemi, Seyyed Mohammad Hassan
Abstract: The local treatment of kojic acid (KA) as a tyrosinase inhibitor results in inadequate skin absorption and a number of side effects. The current study aims to maximize KA skin delivery. To produce KA-hydrogel, 1% KA was injected into a Chitosan/alginate hydrogel. The impacts of biopolymer proportion on the KA-hydrogel preparations were investigated. Swelling analysis, weight loss analysis, differential scanning calorimetry (DSC), scanning electron microscopy (SEM), UV absorption spectroscopy, attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy were used to evaluate the KA-hydrogel. The swelling percentages of KA-hydrogel increased significantly after 4 h. After two weeks, up to 60% of the primary mass of the KA- hydrogel has been removed. By alternation in biopolymer proportion, the drug release profile of KA-hydrogel demonstrated a sustained pattern. According to the skin absorption experiment, KA-hydrogel had higher skin deposition (25.630 ± 3.350%) than KA-plain gel (5.170 ± 0.340%). Moreover, an in vitro cytotoxicity analysis for the modified KA-hydrogel preparations revealed no cytotoxic effects on HFF cell line (90%). Moreover, KA hydrogel had inhibitory effect on melanin synthesis and are comparable with KA. Furthermore, KA-hydrogel had higher inhibitory effect on L-dopa auto oxidation (94.84 ± 2.41%) in comparison KA solution (73.95 ± 3.28%). Also, the dermal irritation study on Wistar rat revealed that the hydrogel constituent used did not irritate the skin. These results revealed that the KA-hydrogel might be employed as KA local administration, thus opening up new prospects for the therapies of hyperpigmentation problems. Abstract : UF0001